Clinical Simulation in Nursing Students' Safe Medication Administration: A Systematic Review - Amir Shahzeydi; Mansour Dianati; Faramarz Kalhor (Wolters Kluwer Medknow Publications, 2024)
Background: Nursing students' safe medication administration is a crucial aspect of ensuring patient safety. Clinical simulation is a novel teaching method applied to reduce factors threatening medication safety in the education of nursing students. Therefore, the aim of the present study was to conduct a review study in this field. Materials and Methods: The present review was conducted using keywords of education, clinical competence, medication safety, medication error, nursing student, clinical simulation, and educational strategies. Suitable articles published between 2000 and 2023 were systematically searched in various national and international online databases, including SID, Magiran, Ovid, Scopus, Web of Science, PubMed, ProQuest, and Google Scholar in both English and Persian languages. Results: A total of 855 articles were retrieved from the initial search findings. After eliminating duplicate and irrelevant articles based on predetermined criteria, a qualitative selection was conducted using CONSORT, MMAT, and JBI critical appraisal checklists. Ultimately, a selection of 11 articles was made, specifically focusing on medication safety education for nursing students through clinical simulation. The findings showed that using clinical simulation improved medication safety and safety knowledge among nursing students. Additionally, this approach was found to enhance their competence in medication administration. Conclusions: Based on the findings, clinical simulation is a safe and effective approach for enhancing nursing students' proficiency in medication safety and administration. Therefore, it is recommended that nursing education authorities implement these findings to improve nursing students' knowledge, performance, and competency in safely administering medications.